(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This study investigates the influence of cooling load on the performance of a portable thermoelectric refrigerator based on the Peltier effect. A compact refrigeration system using a TEC1-12710 thermoelectric module powered at 12 V DC was experimentally analyzed under varying cooling loads, heatsink configurations, and convection modes. The system was divided into a refrigeration compartment and a hot-side heat dissipation area, where three different heatsinks were evaluated under natural and forced convection conditions. Experimental results demonstrate that the thermal characteristics and combination of cooling loads significantly affect the heat transfer rate, the cooling time, and the coefficient of performance. Among the tested configurations, the optimized heatsink operating under forced convection achieved the highest heat transfer rate and coefficient of performance. Tests conducted with various food items and their combinations showed that increased thermal mass results in longer cooling times and higher energy demand. The findings highlight the importance of efficient heat dissipation and load management in improving the performance of portable thermoelectric refrigeration systems, particularly for low-power and mobile applications.